PENGARUH STRES KERJA TERHADAP KINERJA KARYAWAN DENGAN SPIRITUALITAS DI TEMPAT KERJA SEBAGAI VARIABEL MODERATOR PADA DIVISI KELOLA SDM DAN PELAYANAN PELANGGAN PDAM SURYA SEMBADA KOTA SURABAYA - AYU F N A, PRITA (Jurnal Ilmu Manajemen (JIM), 2017)
PDAM Surya Sembada city of Surabaya is the provider and distribution of clean water and drinking water that meets health requirements. Provide excellent service by organizing a good relationship with customers through the provision of accurate information as well as handling complaints quickly and easily with customer satisfaction, as well as always doing repairs that comply with the quality management system ISO 900:2008 and ISO 17025:2005.This research aims to know and explain the influence of job stress onemployees performance with workplace spirituality as a moderator variable in division Human resources management and customer service PDAM Surya Sembada city of Surabaya. This research is a type of causal research that uses a quantitative approach with a population of as many as 135 employees and sampling techniques using a purposive sampling with sample 100 employees in division human resources management and customer service. Techniques Data analysis using software smartPLS. The results of this research show that a negative and significant effect of job stress on employees performance. Workplace spirituality to moderator the influence of job stress on employees performance is not significant. This shows the workplace spirituality not to moderator the influence of job stress on employees performance. Keywords: Job Stress, Workplace Spirituality, Employee Performance